Vocational University Teacher’s Beliefs Upon Business English as a Lingua Franca - Permatasari, Ita; Faizin, Halim Ahmad; Palupi, Dian (PT FORMOSA CENDEKIA GLOBAL, 2023)
English is used globally as a means of communication. In the business context, BELF is used as the framework on how communicating using English among speakers from multicultural background should be done. Since English is a foreign language in Indonesia and was taught in education system, the purpose of the study is to understand teachers or lecturers’ beliefs in BELF. BELF is specifically formulated in the context of business English. Therefore, the participants of this study were those who have experience teaching it. The result indicated that all of the participants teaching practice share the same characteristics with BELF even though they were not familiar with BELF as a term